Pengaruh Faktor Individual Dan Situasional Terhadap Niat Untuk Melakukan Kecurangan Akademis - Annisa Ghaida, Indri; Fontanella, Amy; Sriyuniati, Fera (Akuntansi dan Manajemen, 2020)
This research investigates the effect of individual factors (attitudes, subjective norms and behavioral controls) and situational factors (culture of academic integrity, ambiguity and pressure) towards students' intentions to commit an academic dishonesty. This research was conducted on accounting students at Politeknik Negri Padang (PNP). The data was collected through a questionnaire with total of 346 respondents. The study found that individual factors (attitudes, subjective norms and behavioral controls) have a negative effect on students academis dishonesty. However, situational factors (culture of academic integrity, ambiguity and pressure) did not have a significant effect on the intention to commit an academic fraud. This finding contribute to PNP, especially Accounting department in formulating policies to minimize students’ academic fraud.